Individual tree growth models: Application of the BWINPro7 Simulator - Vargas-Larreta, Benedicto; Corral-Rivas, Javier; Aguirre-Calderón, Óscar; Nagel, Jürgen (Instituto de Ecología, A.C., 2016)
This paper describes a user-friendly computer application developed for forest management planning in El Salto, Durango (Mexico). The computer program BWINPro7 version El Salto allows for forest growth and predicts future stand development. It represents an easy tool that can be used by forest managers and owners of forest lands in the decision-making process. The program incorporates individual tree growth models developed for most pine and oak species during recent years in mixed and uneven-aged forests in the north-eastern region of Mexico. Specifically, the models that were incorporated into the program BWINPro7 are: (1) models to estimate crown width and the height to the live crown base, (2) individual tree basal area and height growth models, and (3) a model to predict individual tree mortality. In addition, the simulator can be used in permanent sample plots to describe stand spatial structure, and to prescribe thinning and timber harvest at industrial scale.